Biopathological Significance of PIWI–piRNA Pathway Deregulation in Invasive Breast Carcinomas - Meseure, Didier (Cancers (Basel), 2020)
SIMPLE SUMMARY: The PIWI-piRNA ribonucleoproteic complexes are pivotal regulators of genome integrity, differentiation and homeostasis and their dysregulation has recently been implicated in carcinogenesis. The aim of this study was to analyze the four PIWILs gene expression in invasive breast carcinomas (IBC) at RNA level using quantitative RT-PCR and protein level using immunohistochemistry. In normal breast tissue, PIWILs 2 and 4 were solely expressed, whereas an abnormal emergence of PIWIL1 and 3 was observed in respectively 30% and 6% of IBCs. Conversely, PIWIL2 was underexpressed in 48.3% and PIWIL4 downregulated in 43.3% of IBCs. Similar patterns of PIWIL deregulation were observed in a multitumoral panel, suggesting a generic mechanism in most cancers. PIWIL2 underexpression was significantly associated with DNA methylation and strong cytotoxic immune response. Characterization of the newly recognized PIWIL-piRNA pathway in IBCs opens interesting therapeutic perspectives using piRNAs, hypomethylating drugs, checkpoints immunotherapies and anti-PIWIL 1–3 antibodies. ABSTRACT: The PIWI proteins emerging in the development of human cancers, edify PIWI-piRNA ribonucleoproteic complexes acting as pivotal regulators of genome integrity, differentiation and homeostasis. The aim of this study is to analyze the four PIWILs gene expression in invasive breast carcinomas (IBCs): at RNA level using quantitative RT-PCR (n = 526) and protein level using immunohistochemistry (n = 150). In normal breast tissue, PIWILs 2 and 4 were solely expressed, whereas an abnormal emergence of PIWIL1 and 3 was observed in respectively 30% and 6% of IBCs. Conversely, PIWIL2 was underexpressed in 48.3% and PIWIL4 downregulated in 43.3% of IBCs. Significant positive associations were observed between PIWIL4 underexpression, HR+ status and HR+ ERBB2+ molecular subtype and PIWIL2 underexpression, PR- status, ERBB2- status and molecular subtype. Similar patterns of PIWIL deregulation were observed in a multitumoral panel, suggesting a generic mechanism in most cancers. PIWIL2-4 underexpression was mainly regulated at epigenetic or post-transcriptional levels. PIWIL2 underexpression was significantly associated with DNA methylation and strong cytotoxic immune response. PIWIL2-4 were mainly associated with genes implicated in cell proliferation. As a result of this study, characterization of the PIWIL-piRNA pathway in IBCs opens interesting therapeutic perspectives using piRNAs, hypomethylating drugs, checkpoints immunotherapies and anti-PIWIL 1–3 antibodies.